A Pilot Evaluation of a Local-Resource-Based Applied Chemistry Module Integrating Metacognition and Chemopreneurship - Muhazam Muhazam; Muhali Muhali; Ika Nurani Dewi; Nova Kurnia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Applied Chemistry practical work can remain procedural when students follow laboratory steps without explicitly regulating their learning or translating chemical evidence into product decisions. This pilot study evaluated students’ perceived practicality of a local-resource-based Applied Chemistry module and examined pretest-posttest changes in metacognitive awareness and chemopreneurship. Twenty-eight undergraduate students enrolled in Applied Chemistry at Universitas Pendidikan Mandalika participated through total sampling during the even semester of the 2025/2026 academic year. The intervention was implemented over seven meetings (21 instructional hours) and involved extraction of local plant materials, formulation of a herbal animal-shampoo prototype, product-quality evaluation, metacognitive reflection, cost analysis, packaging design, and marketing simulation. Data were collected using a 20-item perceived-practicality questionnaire, student worksheet assessments, an adapted 52-item Metacognitive Awareness Inventory, and a 24-item chemopreneurship questionnaire. The instruments were evaluated through expert judgment for content validity, and internal consistency was assessed using Cronbach’s alpha. Data were analyzed using descriptive statistics, Shapiro-Wilk tests, normalized gain calculated from group means, and Wilcoxon signed-rank tests. The mean perceived-practicality score was 82.88% (SD = 4.62), while the mean worksheet score was 79.54 (SD = 3.92). Metacognitive-awareness scores increased from 57.16 to 73.32 (N-gain = 0.38; W = 0, p < .001), while chemopreneurship scores increased from 54.68 to 77.00 (N-gain = 0.49; W = 10, p < .001). These findings indicate favorable student perceptions and higher post-implementation self-report scores. However, the absence of a comparison group and complete psychometric and process evidence limits causal interpretation. Further iterative validation and controlled testing are therefore required.